2012
DOI: 10.1111/j.2047-6310.2012.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

No relation between sleep duration and adiposity indicators in 9–36 months old children: the SKOT cohort

Abstract: Our results do not support the hypothesis that short sleep duration is associated with increased adiposity in this cohort of young Danish children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 13 publications
5
48
1
Order By: Relevance
“…Although longitudinal studies in preschool‐aged children have predominantly suggested that total sleep duration is negatively associated with weight gain overtime or later adiposity, in our study, there was no prospective association between total sleep duration and adiposity after 12 months. Our null association finding is consistent with other two longitudinal studies in Australian (n = 7701) and Danish toddlers (n = 311) . A possible reason for the inconsistent findings between toddlers and preschoolers may be related to the developmental differences .…”
Section: Discussionsupporting
confidence: 89%
“…Although longitudinal studies in preschool‐aged children have predominantly suggested that total sleep duration is negatively associated with weight gain overtime or later adiposity, in our study, there was no prospective association between total sleep duration and adiposity after 12 months. Our null association finding is consistent with other two longitudinal studies in Australian (n = 7701) and Danish toddlers (n = 311) . A possible reason for the inconsistent findings between toddlers and preschoolers may be related to the developmental differences .…”
Section: Discussionsupporting
confidence: 89%
“…We acknowledge that it seems unfeasible to avoid any video dependence for children at present time, but the relationship between video use close to bedtime and short sleep should be stressed. Of note, we did not found any relationship between sleep duration and child BMI, in contrast with the prevalent literature on this topic [26, 27], but in accordance with others [28]. This discrepancy among different studies might be due to variables considered, as it is known that many factors (and video use above all) are related with both sleep and obesity status.…”
Section: Discussionsupporting
confidence: 80%
“…Only six studies used a time diary, or sleep log , and two studies used a validated sleep questionnaire . The objective methods for sleep assessment were rarely used, with two studies reporting the use of actigraphy and another one reporting use of polysomnography for sleep assessment . The variability in the definition of ‘short sleep’, highlighted in nearly all of the reviews published on this topic, was encountered in our meta‐analysis as well.…”
Section: Resultsmentioning
confidence: 94%